Peopleware & heartware - the philosophy of knowledge management - Noordin, Mohamad Fauzan; Othman, Roslina; Zakaria, Noor Azura (2011)
The important of knowledgeable workers (peopleware and heartware) in order to achieve success in knowledge management implementation cannot be doubted. They are the core and backbone to the KM practices in the organization. Therefore, proper plans and strategies should be drawn carefully by the organization to winning the peopleware and heartware prior to the KM implementation. Based on the literature review, this study has highlighted the important of knowledge workers as asset in the organization. Additionally, ideas on how to please this asset to cooperate with the organization to ensure the success of KM practices are given.